SWOT analysis of IEC implementation in RMNCH+A program in Udupi district - Dhange, Vijay; Sumit, Kumar; Pattanshetty, Sanjay M. (International Journal Of Community Medicine And Public Health, 2018)
Background: Information education and communication (IEC) activities in “Reproductive, maternal, newborn, child, and adolescent health programme” (RMNCH+A) plays an important role in creating awareness in the community about the key domains of reproductive and child health. The main purpose of the IEC activities is to bring about changes in knowledge, attitude, belief and behavior of the community towards healthcare. Methods: A qualitative cross-sectional study was conducted among the stakeholders involved in the IEC activities of RMNCH+A programme in Udupi district, Karnataka. In-depth interviews were conducted among the Medical officers, Accredited social health activist (ASHAs) Auxiliary nurse midwifes (ANMs) and lady health visitors (LHV) in the health facilities of Udupi District. Thematic analysis was used for data analysis. Results: Mobilizing the community members and local logistics management at the field level are the main barriers identified in the implementation of IEC activities. Conclusions: It is necessary to leverage and comprehend the strengths of the IEC programs, improvise on the weaknesses, explore the opportunities and minimize the threats associated with the IEC activities under RMNCH+A program.